1999
DOI: 10.1136/hrt.82.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of congenital heart defects and extracardiac malformations associated with chromosomal abnormalities: results of a seven year necropsy study

Abstract: Objective-To analyse the spectrum of congenital heart malformations, the frequency of extracardiac malformations, and the proportion of chromosome aberrations among fetuses sent for necropsy. Material-Necropsies were performed on 815 fetuses-448 induced abortions (55%), 220 spontaneous abortions (27%), and 147 stillbirths (18%)-during a seven year period (1991-97) in the department of pathology of the Charité Medical Centre in Berlin. A congenital heart defect was identified in 129 cases (16%). For all 129 fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
124
4
18

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(172 citation statements)
references
References 25 publications
(13 reference statements)
16
124
4
18
Order By: Relevance
“…Isso é descrito na literatura [26][27][28] e chama atenção para a necessidade de levar em conta o momento do diagnóstico para avaliar a prevalência das diversas apresentações clínicas e sua etiologia.…”
Section: Objetivosunclassified
See 1 more Smart Citation
“…Isso é descrito na literatura [26][27][28] e chama atenção para a necessidade de levar em conta o momento do diagnóstico para avaliar a prevalência das diversas apresentações clínicas e sua etiologia.…”
Section: Objetivosunclassified
“…Entre os NM, a trissomia do cromos- Os defeitos anatômicos mais freqüentemente encontrados tanto entre RNV quanto entre NM foram CIA, CIV e PCA, em concordância com a literatura 12,21,23,[26][27][28] .…”
Section: Objetivosunclassified
“…However, the pathogenesis of CHDs is not fully understood. Population studies have suggested that CHDs are associated with a genetic syndrome (e.g., Down syndrome) or they can be of multifactorial origin, involving genetic and environmental factors (Tennstedt et al, 1999;Botto and Correa, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of minor ECM in children with CHD, was found to be 41.9% by Kramer et al 14 Occurrence of more than 3 minor anomalies has been associated with a major anomaly in 90% of the individuals. In the present study, minor ECM was found in 28% of the study group.…”
Section: Minor Ecmmentioning
confidence: 97%